1993
DOI: 10.1002/ppul.1950160508
|View full text |Cite
|
Sign up to set email alerts
|

The effect of instrumental dead space on measurement of breathing pattern and pulmonary mechanics in the newborn

Abstract: The effect of the instrumental dead space on breathing pattern and the values of pulmonary mechanics was evaluated because of concern about the relatively large dead space of 26 mL in a commercially available system. Sixty-three healthy newborn infants were studied with a system as commercially supplied, and with the dead space eliminated using a 2 L/min biased flow. This led to a significant reduction in mean (+/- SD) values of respiratory rate from 56.8 (+/- 11.7) to 48.2 (+/- 11.7) breath/min (P < 0.0001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 19 publications
(1 reference statement)
1
15
0
2
Order By: Relevance
“…Previous studies reported no adverse effects of a face mask during the first breaths (7)(8)(9)(10)(11)(12)(13)(14). It is possible that the added dead space of the face mask caused carbon dioxide accumulation and influenced the breathing pattern (46,47). However, the wide diameter of the mask reduced rebreathing and firm application of the mask reduced the dead space (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported no adverse effects of a face mask during the first breaths (7)(8)(9)(10)(11)(12)(13)(14). It is possible that the added dead space of the face mask caused carbon dioxide accumulation and influenced the breathing pattern (46,47). However, the wide diameter of the mask reduced rebreathing and firm application of the mask reduced the dead space (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, unavoidable physiological dead space (VD,phys) and dynamic apparatus dead space (VD,ap) comprising alveolar gases that are inhaled a second time into the alveolar compartment, encroach on alveolar ventilation. This influences pulmonary mechanics and breathing pattern [1][2][3][4]. Flow through face masks appears to have significant impact upon dynamic dead space (VD) [5].…”
mentioning
confidence: 99%
“…Although determination of VD,phys is well studied in the literature, there are no studies that measure VD,ap in NIV. However, the use of face masks has the potential to influence VD,ap [1]. In this study, VD,ap is defined as the VD that exceeds VD,phys.…”
mentioning
confidence: 99%
“…Unfortunately, while being very simple, this measurement technique inÂŻuences the very parameters it is designed to measure, respiration being stimulated by irritation of the nucleus trigeminus during facial attachment of the mask [6,7], the additional resistance of the pneumotachometer (RPNT) and, most importantly, the apparatus dead space (VD,app) [8]. The latter is of particular concern in newborns due to their low absolute tidal volumes (5±8 mL .…”
mentioning
confidence: 99%